Specific muscle adaptations in type II fibers after high-intensity interval training of well-trained runners - Kohn, T. A.; Essen-Gustavsson, B.; Myburgh, K. H. (Scandinavian Journal of Medicine & Science in Sports, 2011)
High-intensity interval training (HIIT) forms an important component of endurance athletes' training, but little is known on intramuscular metabolic and fiber type adaptations. This study investigated physiological and skeletal muscle adaptations in endurance runners subjected to 6 weeks HIIT. Eighteen well-trained endurance athletes were subjected to 6 weeks HIIT. Maximal and submaximal exercise tests and muscle biopsies were performed before and after training. Results indicated that peak treadmill speed (PTS) increased (21.0 ± 0.8 vs 22.1 ± 1.2 km/h, P<0.001) and plasma lactate decreased at 64% and 80% PTS (P<0.05) after HIIT. Cross-sectional area of type II fibers tended to have decreased (P=0.06). No changes were observed in maximal oxygen consumption, muscle fiber type, capillary supply, citrate synthase and 3-hydroxyacetyl CoA dehydrogenase activities. Lactate dehydrogenase (LDH) activity increased in homogenate (P<0.05) and type IIa fiber pools (9.3%, P<0.05). The change in the latter correlated with an absolute interval training speed (r=0.65; P<0.05). In conclusion, HIIT in trained endurance runners causes no adaptations in muscle oxidative capacity but increased LDH activity, especially in type IIa fibers and in relation to absolute HIIT speed.